2004
DOI: 10.1002/hc.20004
|View full text |Cite
|
Sign up to set email alerts
|

Novel conversion of 6H‐1,3,5‐oxathiazine S‐oxides into 5‐membered heterocyclic compounds

Abstract: 5H-1,2,4-oxathiazoles were efficiently synthesized from 6 H-1,3,5-oxathiazine S-oxides by thermal cycloreversion of the substrates and the products were effectively converted into 1,2,4-thiadiazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…11 Other more complicated methods are also reported: from the corresponding oxathiazolone, 12 benzenecarboximidamide and diethyl azodicarboxylate, 13 or from 1,2,4-oxathiazoles and Lewis acid. 14 Thermal cycloreversion of 6 H -1,3,5-oxathiazine S -oxides followed by ring closure of the resulting intermediates is also reported to yield 1,2,4-thiadiazoles. 15 More recently, Khosropour and Noei described the preparation of 1,2,4-thiadiazoles using 2,4,6-trichloro-1,3,5-triazine, DMSO and polyethylene glycol 400.…”
Section: Resultsmentioning
confidence: 98%
“…11 Other more complicated methods are also reported: from the corresponding oxathiazolone, 12 benzenecarboximidamide and diethyl azodicarboxylate, 13 or from 1,2,4-oxathiazoles and Lewis acid. 14 Thermal cycloreversion of 6 H -1,3,5-oxathiazine S -oxides followed by ring closure of the resulting intermediates is also reported to yield 1,2,4-thiadiazoles. 15 More recently, Khosropour and Noei described the preparation of 1,2,4-thiadiazoles using 2,4,6-trichloro-1,3,5-triazine, DMSO and polyethylene glycol 400.…”
Section: Resultsmentioning
confidence: 98%
“…However, the comparable yields were afforded when the aforementioned reactions were carried out at toluene refluxing temperature for 2 h (Table , runs 11–15). In the 1 H NMR spectrum of the aforementioned crude products, we did not observe any peak responsible for 3,5‐diphenyl‐1,2,4‐thidiazole 8 , that was the main product of 4 with silica gel . These results suggest that at high temperature, the compound 5 does not give any deoxygenated product 4 .…”
Section: Resultsmentioning
confidence: 70%
“…6 H ‐1,3,5‐Oxathiazines 1 were prepared by treating an aryl thioamide with an aliphatic aldehyde and BF 3 .OEt 2 according to the reported procedures . We found that treatment of 1 with 1.1 equiv of m ‐CPBA at 0 °C for 1 h afforded 2 in quantitative yield . Accordingly, we took an attempt to synthesize 3 by two step successive oxidation of 1 using 1.1 equiv m ‐CPBA, but in contrast to our expectation, we have 5 H ‐1,2,4‐oxathiazole S ‐oxide 5 in quantitative yield instead of desired 3 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the case of oily compound 3z , it was purified by silica gel chromatography using hexane-ethyl acetate (9:1). Compounds 3a , 33,34 3b , 35,36 3e , 37 3f , 3g , 38 3h , 39 3d , 40 3s , 41 3c , 42 3ff, 43 3jj, 44 3kk 45 have previously been reported.…”
Section: Methodsmentioning
confidence: 94%